Delayed delivery of the two remaining fetuses of triplet pregnancy: Case Report - Abdelazim, Ibrahim A.; Al-Munaifi, Sulaiman (Gynecology Obstetrics & Reproductive Medicine, 2019)
The incidence of multiple gestations increased after introduction of assisted reproduction techniques. Traditionally; in twin and/or triplet pregnancies; if one baby delivered preterm, this situation managed by delivery of the second and/or the third fetuses. This case report represents the suggested conservative management during the delayed delivery of the two remaining fetuses of triplet pregnancy, its outcome, and benefits. The studied woman is 35-years old, G3 P2, triplet pregnancy after intra-cytoplasmic sperm injection trial, presented with preterm premature rupture of membranes of the first fetus at 20+2 weeks` gestation, who delivered as fresh still birth. The couple informed, and agreed for the conservative management of the two remaining fetuses. After delivery of the first fetus; the umbilical cord ligated as high as possible in the cervix. She received systemic antibiotics for one week, with follow up of; infections, and consumptive coagulopathy parameters, and wellbeing of the fetuses through the conservative treatment. She received betamethasone to accelerate the lung maturity, and Mg-Sulphate for fetal neuro-protection at 24 weeks. The conservative management discontinued, and she delivered by cesarean section at 25 weeks+1 after attack of ante-partum hemorrhage. The delivered neonates admitted to neonatal intensive care unit on ventilator support, surfactant therapy, and antibiotics. 80 days after neonatal intensive care unit admission; the neonates discharged from the neonatal intensive care unit with corrected age of 36 weeks+, on complete oral feeding, and room air. The first fetus delivered at 20 weeks+2, fresh still birth (410 g), while the second, and third fetuses delivered at 25 weeks+1 (34 days of the conservative management), 780, and 840 g; respectively. Both fetuses survived, discharged from the neonatal intensive care unit after 80 days, at 2.2, and 2.3 kg weight; respectively. The birth weight, and the survival rate of both fetuses increased after the conservative management. The suggested conservative management of the delayed delivery may be associated with reduced neonatal mortalities without any maternal complications.